1991
DOI: 10.1172/jci114968
|View full text |Cite
|
Sign up to set email alerts
|

Protein heterogeneity in the human Ro/SSA ribonucleoproteins. The 52- and 60-kD Ro/SSA autoantigens are encoded by separate genes.

Abstract: Two cDNA clones encoding the 52-kD form of a protein present in human Ro/SSA ribonucleoprotein complexes were cloned from a X gtl1 human thymocyte cDNA library. These clones reacted with lupus patient sera which had anti-52-kD Ro/SSA antibodies, and with affinity-purified anti-52-kD Ro/ SSA antibodies. Moreover, affinity-purified antibodies isolated from isopropyl-l-D-thiogalactopyranoside-induced proteins of these clones reacted only with the 52-kD protein of lymphocytes in Western blots and precipitated Ro/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(67 citation statements)
references
References 64 publications
1
66
0
Order By: Relevance
“…However, it is possible that 52-kd RolSS-A protein is not precipitable under these conditions. Although it is also possible that 52-kd RolSS-A protein was not readily labeled, this possibility seems remote because the 52-kd RolSS-A contains methionine (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that 52-kd RolSS-A protein is not precipitable under these conditions. Although it is also possible that 52-kd RolSS-A protein was not readily labeled, this possibility seems remote because the 52-kd RolSS-A contains methionine (13).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations will be undertaken to characterize the other members of the enterophilin family. Accordingly, it is interesting to note that multiple transcripts have already been reported for other members of the B30.2 family such as Ro/SS-A, RoRet, or MID1 (30,(63)(64)(65). For the latter gene, other mutations responsible for Opitz syndrome were recently described, and authors reported the presence of at least six isoforms of mRNA (66).…”
Section: Fig 5 Expression Of Enterophilin-1 Along the Small Intestimentioning
confidence: 93%
“…The 52kD polypeptide is alternatively spliced, yielding an isoform that lacks aminoacids 169-245 of the full-length protein (Chan et al 1995). Although their function is not yet known, both the 60 and the 52 kD Ro have zinc finger motifs capable of binding DNA and regulating gene expression (Chan et al 1991, Itoh et al 1991. The anti-La/SSB is another auto-antibody found in the serum of mothers and affected children.…”
Section: The Neonatal Lupus Syndromementioning
confidence: 99%